TINDAKAN KEPOLISIAN RESOR LABUHANBATU DALAM PENANGANAN PELANGGARAN LALU LINTAS - Yustina Yustina; Maidin Gultom; Bachtiar Simatupang (JURNAL PROINTEGRITA, 2019)
The purpose of this research was to find out and understand the causes of traffic violations in the jurisdiction of Labuhanbatu Resort Police, the criminal liability of traffic violators that resulted in deaths in traffic accidents, overcoming traffic violations in the jurisdiction of Labuhanbatu Resort Police.Research results show that the factors causing traffic accidents are usually classified as identical to the elements of the transportation system, namely road users, drivers and pedestrians, vehicles, roads and the environment, or a combination of two or more elements. The criminal liability of traffic violators which results in deaths in traffic accidents, in addition to imprisonment, confinement, or fines, traffic criminals can be subjected to additional criminal sanctions in the form of revocation of a driver's license or compensation caused by traffic crime.